Interactivity, Marketing Communication, and Emerging Markets: A Way Forward. Issue 1 (2nd January 2017) - Schultz, Don E.; Malthouse, Edward C.
ABSTRACT: This managerial article develops a conceptual model that illustrates the similarities and differences between marketing communication (marcom) models used in established markets and what is and will likely be needed in emerging markets. We argue that existing marcom models often fail in new markets because of the culture, technology, consumer interactivity, reciprocity, networks, and channels found in them. A new approach based on the needs, capabilities, and requirements of emerging markets are proposed. Termed the consumer networks and negotiation (CN 2 ) approach, it is based on the unique situations often found in emerging markets. Since the effectiveness of existing established marcom models appears to be declining in American and European markets, this model could also help experienced marketers rethink their approaches as well. Recommendations for further development and testing of the models are proposed.